Blockchain-Based Evidence Legality in Indonesia's Criminal Justice System - Naseer, Muchammad; Gusdevi, Harya; Rahayudin, Rahayudin; Guterres, Antonio (Riviera Publishing, 2026)
This study aims to analyze the legality of blockchain-based digital evidence in criminal justice processes in Indonesia, emphasizing two main focuses: the possibility of its admissibility as valid evidence and the identification of accompanying normative, technical, and procedural limitations. This study uses a normative juridical method through a legislative approach (the ITE Law, the Personal Data Protection Law, the Criminal Procedure Code, and Supreme Court Regulations), a conceptual approach (the concept of digital evidence, blockchain technology, and audit trails), a comparative approach (comparison of practices in several other jurisdictions), and a case approach through analysis of court decisions relating to electronic evidence. The results show that blockchain technology has significant potential to be recognized as evidence with strong probative value due to its characteristics of immutability, transparency, and traceability. However, this study also identifies several challenges, including the lack of specific regulations in the Criminal Procedure Code, potential conflicts with the principle of personal data protection, the absence of uniform digital audit trail standards, the heterogeneity of blockchain systems, and the limited technical capacity of law enforcement officials. These findings underscore the urgency of regulatory reform, standardization of evidentiary procedures, and strengthening the technical competence of law enforcement officials so that blockchain-based evidence can be implemented effectively and accountably in criminal proceedings. Practically, the results of this study provide a basis for policymakers to formulate a legal framework and technical policies that adapt to the use of blockchain technology in the criminal evidence system without neglecting the principles of human rights protection and legal certainty. Overall, this study contributes conceptually and normatively to the integration of blockchain technology into the Indonesian criminal justice system.